Risk Management Analysis of the Clean Water Pipeline Construction Project of PT CATL Karawang Using the HIRARC Method - Aminatuz Zuhriyah; Hanie Teki Tjendani; Sajiyo Sajiyo (Transpublika Publisher, 2025)
Construction activities for water pipeline projects in industrial facilities present various occupational and operational hazards that may disrupt project performance if not properly controlled. This study aims to analyze the occupational risks associated with the water pipeline construction project of PT CATL Karawang using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method. The research was conducted through field observation, work breakdown structure analysis, and semi quantitative risk assessment based on likelihood and severity scoring. The results indicated ten (10) dominant hazards across five (5) major activities including trench excavation, pipe lowering, pipe joint installation, backfilling and compaction, pressure testing, and site restoration. Three (3) risks were categorized as high level, namely trench collapse, pipe dropping during lifting, and stuck by heavy equipment, while the remaining risks were classified as medium level. Appropriate risk controls are recommended following the hierarchy of control, emphasizing engineering controls, administrative procedures, and mandatory use of personal protective equipment. The study concludes that the overall risk category of the project is moderate, high and requires consistent monitoring and implementation of control measures to reduce the probability of incident and ensure safe and continuous project execution.